Therapeutic Use of Silver Nanoparticles in the Prevention and Arrest of Dental Caries - Claudia Butrón Téllez Girón; Juan F. Hernández Sierra; Idania DeAlba‐Montero; María de los A. Urbano Peña; Facundo Ruiz (Bioinorganic Chemistry and Applications)
Dental caries is one of the major diseases of the oral cavity affecting humans worldwide. Different alternatives have been used for its control, but its incidence and prevalence are still high. On the other hand, silver has been used for centuries due to its antimicrobial properties. With advances in nanotechnology, the use and research in nanomaterials has increased, recently, and silver nanoparticles have become an essential part of the dental practice, giving materials physical and chemical improvements in their properties, used for their antibacterial capacity preventing and arresting dental caries. The objective of this review was to examine the use of silver nanoparticles, in the treatment of dental caries in the remineralization of teeth hard tissues, as well as the antimicrobial potential, cytotoxicity, and long-term effectiveness.